Застосування інсуліну гларгін (Лантус®) у повсякденній клінічній практиці: результати обсерваційного перехресного ретроспективного спостереження IDEAL - Ларін, О. С. (Clinical Endocrinology and Endocrine Surgery, 2013)
Diabetes mellitus (DM) type 2 is one of the most important problems of present-day medicine. The main reasons for limiting the use of insulin therapy are: the risk of hypoglycemia, body weight increase, a peak of the insulin activity, starting treatment with sub-optimal dose of insulin and its inadequate titration. Insulin glargine (Lantus®) is the first long-acting insulin analogue, characterized by the peak of activity miss and less interindividual variability compared with insulin neutral protamine Hagedorn (NPH) or ultralente. Objectives – evaluate the efficacy and safety of insulin glargine (Lantus®), and NPH insulin in patients with DM type 2 in daily clinical practice. In a observational retrospective cross follow study included 216 patients treated with Lantus® for 4-9 months (active group) and 133 patients treated with NPH insulin for more than 12 months (control group). Efficacy was assessed by the level of glycosylated hemoglobin (HbA1c) and fasting glucose. Safety was assessed by evaluating the frequency of documented symptomatic hypoglycemia. The groups were homogeneous by sex and age. The reasons for changing to Lantus® were decompensation or labile for DM (48.03%), allergy or intolerance to NPH insulin (1.18%), comorbidity (1.18%). By the end of the study among patients treated with Lantus®, the number of patients with a value of HbA1c more than 7.5% decreased by 47.1%, whereas in the NPH insulin group – by 10.3%. The number of patients with a fasting glucose level of more than 7 mmol/l Lantus® group decreased by 42.1% and in the group of NPH insulin – by 15.5%. The mean daily insulin dose in patients treated with Lantus® was lower than average daily dose in control group for 22.2%. Symptomatic hypoglycemia during the last month of observation occurred significantly more often in the control group (62.05%), whereas in the main group – 37.96% (p<0.05). Lantus® versus NPH insulin allows a better compensation of DM 2 and requires a smaller daily dose of insulin.